La patria nueva : economía, sociedad y cultura en el Perú, 1919-1930 - Drinot, Paulo (Serie Historia y ciencias sociales., 2018)
The "La Patria Nueva" of Augusto B. Leguia (1919-1930) continues to be the longest-lasting government in Peruvian republican history. Also known as the "Oncenium", the period constitutes a key moment in the 20th century. However, although historians and the general public acknowledge this, little is known about that situation. And, even worse, what little we know responds, to a large extent, to the "black legend" that began to form after its collapse in 1930, if not before. Through specific studies - more than from the great interpretation - and mobilizing various methodologies and theoretical perspectives, this book proposes a new way of observing this crucial period of republican life and opens new avenues of research on the "La Patria Nueva".